ANALISIS KELAYAKAN FINANSIAL PADA INDUSTRI RUMAH TANGGA TAHU “TALISE” DI KECAMATAN MANTIKULORE KOTA PALU SULAWESI TENGAH - A, Novitasari; Laapo, Alimudin; Sulaeman, Sulaeman (AGROTEKBIS, 2018)
The objective this research is to analyze financial feasybility to Tofu Home Industrian ‘Talise” based on criteria Net Present Value (NPV), Net B/C Ratio and Internal Rate of Return (IRR). This research was conducting on March to April 2015, respondent in the research choose by porpusive. Respondent in this research consist of 4 people, a leader and three employes, two of them work in production and one else work as marketing. Method of analysis use in this research is analysis finansial feasybility. The result of this research show that value Net Present Valueis Rp13,927,446, Net B/C Rasio 1.40, and Internal Rate of Return25.72 %. The result indicate that “Talise” Tofu Home Industry is feasible.   Key words : Feasibility of  Finansial, Home Industry, Tofu.